The Impact of Combined Oral Sildenafil and Inhaled Nitric Oxide for Treating Persistent Pulmonary Hypertension of the Newborn: A Single Center Experience - Hayriye Gozde Kanmaz; Mehmet Büyüktiryaki; Şerife Suna Oğuz; Evrim Dizdar Alyamac; Fatma Nur Sarı; Fuat Emre Canpolat; Nurdan Uras (Medical Network, 2017)
Objective: We aimed to compare the effect of the combined therapy, sildenafil and inhaled nitric oxide with inhaled nitric oxide monotherapy for the treatment of Pulmonary Hypertension of the Newborn. Study Design: Newborn infants (gestational age greater than 34 weeks) who were diagnosed with pulmonary hypertension between December 2008 and 2010 were retrospectively evaluated. Group I (n=14) received monotherapy with inhaled nitric oxide and Group II (n=9) received combined therapy with inhaled nitric oxide and oral sildenafil. Primary outcome was to compare the duration of inhaled nitric oxide therapy between groups. Results: Demographic characteristics were similar between the groups. Combination therapy was associated with early weaning of inhaled nitric oxide (4.8±1.5 vs. 13.5±7.6 hours). The duration of inhaled nitric oxide therapy was slightly shorter in combined therapy group (75[24-125] vs. 109[24-210] hours), however, the difference was insignificant (p=0.2). The incidence of mortality and neonatal outcomes were similar between the groups (p>0.05). Conclusion: Combined therapy did not result in shorter duration of inhaled nitric oxide therapy. Further well designed and larger studies that will elucidate the benefits of combination therapies and optimal therapy whereinhaled nitric oxide is not available are warranted.